2021
DOI: 10.1177/0363546521995512
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging 1 Year After Hamstring Autograft Anterior Cruciate Ligament Reconstruction Can Identify Those at Higher Risk of Graft Failure: An Analysis of 250 Cases

Abstract: Background: There is currently no analysis of 1-year postoperative magnetic resonance imaging (MRI) that reproducibly evaluates the graft of a hamstring autograft anterior cruciate ligament reconstruction (ACLR) and helps to identify who is at a higher risk of graft rupture upon return to pivoting sports. Purpose: To ascertain whether a novel MRI analysis of ACLR at 1 year postoperatively can be used to predict graft rupture, sporting level, and clinical outcome at a 1-year and minimum 2-year follow-up. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 33 publications
(50 reference statements)
6
28
0
1
Order By: Relevance
“…Among studies investigating ACL graft structure and remodeling using MR imaging, some have reported signal measurements from different locations of the ACL graft. [14][15][16]18,21 Li et al [14][15][16] utilized the signal-to-noise quotient (SNQ), another method to normalize graft signal intensity, at the femoral, middle, and tibial regions from a single midsagittal slice. While their results showed regional differences in SNQ, [14][15][16] none of the studies conducted statistical comparisons of average SNQ among the 3 regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among studies investigating ACL graft structure and remodeling using MR imaging, some have reported signal measurements from different locations of the ACL graft. [14][15][16]18,21 Li et al [14][15][16] utilized the signal-to-noise quotient (SNQ), another method to normalize graft signal intensity, at the femoral, middle, and tibial regions from a single midsagittal slice. While their results showed regional differences in SNQ, [14][15][16] none of the studies conducted statistical comparisons of average SNQ among the 3 regions.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested differences in average T 2 * measurements between the proximal half and distal half of the grafts, which were not statistically compared. Most recently, Putnis et al 21 used discrete 2-dimensional measurements to investigate regional differences in relative ACL graft to posterior cruciate ligament signal intensity ratio (SIR) in reconstructed knees 1 year after surgery. They showed significant differences in graft SIR, with the highest signal in the middle region and the lowest in the femoral aperture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In the present study, 1 patient was excluded for graft rupture, the 1-year MRI scan demonstrated a high proximal graft signal, which has previously been shown to correlate with risk of rupture. 26 In this series, KT-1000 arthrometer measurements were not correlated with graft MRI signal at 1 year or signal change thereafter and had no correlation with PROMs at any time point. Currently, KT-1000 arthrometry is still being used to demonstrate a difference between laxity of healthy and operated legs, with \3 mm difference historically described as an indicator for a stable knee.…”
Section: Discussionmentioning
confidence: 52%
“…According to our study, all-inside and standard ACLR exhibited the worst maturity in the middle graft region, followed by the graft near the femoral tunnel; the tibial side showed the best maturity. Putnis et al [ 26 ] determined that the graft signal near the tibial tunnel was significantly lower than that of the femoral side. As the middle region of the graft is the primary area subjected to distraction forces and is far from the tunnel, graft hematologic reconstruction may be slower than the two ends.…”
Section: Discussionmentioning
confidence: 99%